From Physicochemical Classification to Multidimensional Insights: A Comprehensive Review of Uremic Toxin Research - Mario Cozzolino; Lorenza Magagnoli; Paola Ciceri (Toxins)
Chronic kidney disease (CKD) is a global health burden, with uremic toxins (UTs) playing a central role in its pathophysiology. In this review, we systematically examined the evolution of UT classification from the 2003 European Uremic Toxin Work Group (EUTox) system based on molecular weight and protein-binding properties to the 2023 multidimensional framework integrating clinical outcomes, clearance technologies, and artificial intelligence. We highlighted the toxicity mechanisms of UTs across the cardiovascular, immune, and nervous systems and evaluated traditional (e.g., low-/high-flux hemodialysis) and advanced (e.g., high-cutoff dialysis and hemoadsorption) clearance strategies. Despite progress, challenges persist in toxin detection, clearance efficiency, and personalized therapy. Future directions include multi-omics-based biomarker discovery, optimized dialysis membranes, advanced adsorption technology, and AI-driven treatment personalization. This synthesis aims to bridge translational gaps and guide precision medicine in nephrology.